Implementation of the Values ​​of the Pancasila Student Profile Strengthening Project (P5) at M. Hilir Ismail Kindergarten, Bima City - Sabila Sabri Rahmani; Ahmadin; Syahru Ramadhan (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to explore the implementation of values in the Pancasila Student Profile Strengthening Project (P5) at M. Hilir Ismail Kindergarten, Bima City. P5 is an initiative of the Ministry of Education and Culture that aims to strengthen character building and Pancasila values in early childhood. The background of this research is based on the importance of strengthening children's character from an early age through education based on the values of the Pancasila learner profile which is the main achievement in the implementation of an independent curriculum, especially in facing the challenges of globalization and rapid social change. M. Hilir Ismail Kindergarten in Bima City as an early childhood education institution plays a vital role in the application of the P5 values through various activities that integrate Pancasila characters and attitudes in children's daily lives. The research method used is a qualitative approach with collection techniques through observation, interviews, and documentation. Researchers observed learning activities and teacher and child interactions in carrying out P5 activities at M. Hilir Ismail Kindergarten with a focus on the implementation of Pancasila learner profile values taught to children. The results showed that activities such as praying together, playing sharing, and simulating professions succeeded in instilling Pancasila values such as mutual cooperation, honesty, tolerance, and justice. Children also showed improvement in character aspects.